A comparative study of social networks' utilisation and addiction among undergraduate and postgraduate students in Nigerian Universities (2013)
This study investigated social media utilisation and addiction among students in Nigerian universities. The survey research design was adopted while questionnaire was used as the main instrument of data collection. The sample for the study comprises three hundred and twenty seven (32 7) students randomly selected across five selected universities in Nigeria but only 215 of the students provided useful responses for the study. Five research questions were answered in the study. The study revealed regular use of social media for the purpose of communicating and connecting with friends only while Picassa, Twitter, Flickr, Youtube MySpace, Blogger, Linkedln and Library Thing were found to top the list of social media being used on regular basis by the students. The level of social media addiction among the students was found to be low. The study revealed that there is no significant difference in the level of addiction to social media between undergraduate and postgraduate students. On the other hand, the study established a significant difference in the level of social media utilization between undergraduate and postgraduate students in Nigerian universities as the undergraduate students were found to utilize social media more than their postgraduate counterparts.